Impact of radiative forcing of spatially varying CO2 concentrations on net primary production - Peng, Jing; Dan, Li; Tang, Xiba; Yang, Fuqiang (Frontiers in Earth Science, 2022)
The radiative forcing of spatially varying carbon dioxide (CO2) concentrations has modified the climate by altering surface energy, the water budget, and carbon cycling. Over the past several decades, due to anthropogenic emissions, atmospheric CO2 concentrations in the whole terrestrial ecosystem have become greater than the global mean. The relationship between climatic variables and net primary production (NPP) can be regulated by the radiative forcing of this spatial variation. The present results show that owing to the radiative forcing of spatially varying CO2 concentrations, NPP has reduced globally by −0.6 Pg C yr−1. Region 2, with increased CO2 and decreased NPP, shows the greatest reductions, by −0.7 Pg C yr−1. Variations of both NPP and CO2 concentrations are distributed asymmetrically. As human activities are mainly located in the Northern Hemisphere, increased CO2 has mainly manifested in these regions. Especially in region 2, with increased CO2 and decreased NPP, increasing downward longwave radiation has heated the ground surface by 2.2 W m−2 and raised surface temperatures by 0.23°C. At the same time, due to the radiative forcing of spatial variations in CO2 concentrations, local dependence of NPP on soil moisture has increased due to enhanced temperature and evapotranspiration coupling, which may improve negative NPP anomalies locally, especially in region 2. With continued increasing CO2 concentrations, its spatial variation due to radiative forcing is likely to amplify warming and have a negative impact on NPP in the terrestrial ecosystem.